ANALISIS CEMARAN MIKROBA PADA LEMPUK DURIAN SEBAGAI OLEH-OLEH KHAS PEKANBARU - Wahyu Margi Sidoretno; Muhammad Azhari Herli (LPPM Universitas Abdurrab, 2017)
Tourism sector is an important thing in economy growth of an area. The safety of food products from tourism areas have to be increased. A bad quality food product (does not meet the qualification, safety, and contamination of pathogen microorganism) can cause some poisoning cases that is one of society health problems. Lempuk durian, made from durian and sugar, is a food product from Pekanbaru which is demanded. Beside of the sweet taste, the product has a good and delicious taste. This research aimed to increase the food safety of lempuk durian, so societies can be avoided from food poisoning because of pathogenic microorganisms. The result was compared with lempuk durian safety standard by SNI- 01- 4313- 1996. The microorganism contamination was determined using Total Disk Number method, and Coliform and Coliform fecal was measured with Most Probable Number method. The results obtained for ALT (total plate number) of samples A through E still meet the requirements required by SNI 7388 of 2009 on the maximum limit of microbial contamination in food that is 104 colonies / g and for MPN sample C that does not meet. Keywords: Lempuk durian, Total Plate Number, Most Probable Number, Coliform-Colifecal